Overview of the Effectiveness of Light Emitting Diode (LED) and Compact Fuorescent Lamp (CFL) Phototherapy on Neonatory Jaundice Bilirubin Levels - Tia Setiawati; Maya Amalia; Sipa Dwi Astuti (Indonesian Journal of Global Health Research, 2025)
Neonatal jaundice is the condition of a newborn with high levels of bilirubin, which can cause various negative impacts on the baby, such as neurological abnormalities, mental retardation and seizures. The main treatment that can be done is by administering light phototherapy. Preliminary studies in the city of Bandung, there are still hospitals in Bandung that use phototherapy with the Compact Flourescent Lamp (CFL) type of lamp and there are also hospitals that use phototherapy with the Light Emitting Diode (LED) type. Objective: The aim of this research is to identify the effectiveness of LED and CFL phototherapy in reducing bilirubin levels in babies with neonatal jaundice in Bandung City. Method: This research method is a quasi-experiment with a retrospective approach. The sample for this study was 72 babies who were given phototherapy from January to July 2023. The data collection technique used data recorded at hospitals in Bandung City. Data was collected with checklist sheets and data analysis using the independent sample t test. The research locations were Bandung Kiwari Hospital and Bandung Muhamadiyah Hospital. Results: The results of the independent t-test showed a significant difference in total serum bilirubin values in the two groups before and after phototherapy (sig coefficient = 0.000 < 0.05). The group of neonates with CFL had a bilirubin value of 9.3989 which was higher compared to the group of neonates with LED phototherapy, namely 6.4189. LED phototherapy is more effective in reducing bilirubin compared to CFL phototherapy. Conclusions: Hospital policies to add LED phototherapy facilities can be considered, because they are more effective in reducing bilirubin levels.